ANTIBACTERIAL ACTIVITY OF METHANOLIC EXTRACTS OF ZEPHYRANTHES CANDIDA - Sindiri, Manoj Kumar; Machavarapu, Manasa; Vangalapati, Meena (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: To evaluate the anti-bacterial activity. Methods: Zephyranthes candida is a perennial herb, used as folk medicine in many countries. In the present study antibacterial activity of methanolic extract of Z. candida leaves was evaluated against Bacillus subtilis, Klebsiella pneumonia, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aereus and Enterobacter aerogenes bacterial strains by Agar well diffusion method. Methanol was used as control for this study. Results: The inhibition zones for bacterial strains were found to be 0 mm, 3 mm, 8.5 mm, 6 mm, 8 mm and 7 mm respectively. Conclusion: From the outcomes of this study Z. candida shows antibacterial activity. Key words: Zephyranthes candida, methanolic extract, Bacillus subtilis, Klebsiella pneumonia, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aereus, Enterobacter aerogenes